Soft skills profile of vocational school students in Yogyakarta City for entering the industrial world - Tri Wulaningrum; Samsul Hadi (Jurnal Pendidikan Vokasi, 2019)
This study aims to determine the profile and how much the level of soft skills of Vocational High School students in Yogyakarta City. This study is survey research. The population of this study was all students grade XI of State Vocational Schools in Yogyakarta City. The sample of this study was 990 students. The data were collected using a questionnaire. The data were then analyzed and presented in a percentage form. The results of the study present that the percentage gain shows the soft skill profile of Vocational High School students in Yogyakarta City in each aspect, namely communication/persuasion skills of 75.19%; performance management skills of 77.22%; self management skills of 70.27%; interpersonal skills of 78.68%; leadership/organizational skills of 77.85%; and cultural skills of 75.60%. Then, the level of soft skills ability of Vocational High School students in Yogyakarta City is generally categorized in medium, which is in the profile range between M-0.5SD and M + 0.5SD (M - 0.5SD < x < M + 0.5SD).